2016
DOI: 10.1097/j.pain.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, impact, and predictors of persistent pain after root canal treatment

Abstract: Root canal treatment (RCT) is commonly performed surgery and persistent pain is known to occur, but little is known about how these patients are affected by this pain. While biopsychosocial mechanisms are thought to be associated with the development of such pain, similar to persistent pain following surgery in other body sites, little is known about the baseline predictors for persistent pain. We assessed the frequency of persistent pain 6 months following RCT, measured the impact this pain had on patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 29 publications
0
74
0
Order By: Relevance
“…Of those 354 patients, 38 (11%, 95% CI: 8-14%) met criteria for pain at 6 months following RCT and were considered eligible cases, which was slightly higher than 10.0% observed over the entire (“parent”) study population (3). Only subjects that had consented to be contacted were invited to participate in this study.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Of those 354 patients, 38 (11%, 95% CI: 8-14%) met criteria for pain at 6 months following RCT and were considered eligible cases, which was slightly higher than 10.0% observed over the entire (“parent”) study population (3). Only subjects that had consented to be contacted were invited to participate in this study.…”
Section: Resultsmentioning
confidence: 86%
“…Persistent pain after RCT is known to occur and is not an uncommon event, being estimated by meta-analysis to be 5.4% (2) and by prospective observation to be 10.0% at 6 months following RCT (3). Taxonomy of diagnoses underlying persistent pain after RCT can be broadly classified as either odontogenic (4) or nonodonogentic (5) in etiology.…”
Section: Introductionmentioning
confidence: 99%
“…The present report is based on secondary analyses of data originally collected. The original study was designed to prospectively assess outcomes following root canal treatment (RCT), and details of study methods (18) and outcomes (1922) have been previously reported. In brief, 62 dentists (46 general practitioners and 16 endodontic specialists) from 5 regions (Alabama/Mississippi, Florida/Georgia, Minnesota, Oregon/Washington, and Denmark/Sweden) participated by collecting observational data from endodontic patients in their practices.…”
Section: Methodsmentioning
confidence: 99%
“…A prospective study of pain before and after RCT concluded that 10% of the patients still experienced pain 6 months post‐treatment (Nixdorf et al . ). In a retrospective study, 45% of patients had experienced painful episodes from a root filled tooth with a persisting endodontic lesion up to 20 years post‐treatment (Yu et al .…”
Section: Introductionmentioning
confidence: 97%
“…, Nixdorf et al . ), and also attempted to identify the cause of such pain (e.g. remaining infection or nonodontogenic pain) (Nixdorf et al .…”
Section: Introductionmentioning
confidence: 99%